2006
DOI: 10.1007/s10311-006-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Kraft E1 and black liquor effluents by biological and chemical processes

Abstract: We sutdied the application of the bacteria Azotobacter vinellandi on the treatment of effluents from pulp and paper industry. Two types of treatment employing this microorganism were studied: biological treatment isolated and combined with stages of pre-or post-treatment using ozonation or photocatalysis processes. In the biological treatment, the siderophores production by A. vinellandi had a major effect on the efficiency of effluents degradation. Among the different combined treatments, the best results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In addition, a 45% mineralization enhancement was also reported in this essay for the pre-biological treatment of kraft effluent by photocatalysis (Moraes et al 2006) (Table 4).…”
Section: Semi-conductor Photocatalytic Processessupporting
confidence: 71%
“…In addition, a 45% mineralization enhancement was also reported in this essay for the pre-biological treatment of kraft effluent by photocatalysis (Moraes et al 2006) (Table 4).…”
Section: Semi-conductor Photocatalytic Processessupporting
confidence: 71%
“…Moraes et al (2006) achieved good efficiencies (75% color removal and an increase of mineralization of the 140% with respect to the previous biological treatment) in the application of photocatalysis as post-biological treatment of black liquor. In addition, a mineralization increase of the 45% was obtained for the pre-biological treatment of kraft effluent by photocatalysis (Moraes et al 2006). Notably, Merayo et al (2013) did not find any significant benefit of photocatalysis either before or after biological treatment, whereas ozone was found to be quite effective as a post-treatment.…”
Section: Uv-catalysis (With Tio2 or Peroxide)mentioning
confidence: 91%
“…Jamil et al (2011) reported 0.25, 0.45, and 0.7 increases of the BOD5/COD ratio for the treatment of an effluent from a board paper mill by UV, UV/H2O2, and photoFenton processes, respectively; as well as a significant destruction of aromatic chlorinated compounds in all the trialed photocatalytic processes. Moraes et al (2006) achieved good efficiencies (75% color removal and an increase of mineralization of the 140% with respect to the previous biological treatment) in the application of photocatalysis as post-biological treatment of black liquor. In addition, a mineralization increase of the 45% was obtained for the pre-biological treatment of kraft effluent by photocatalysis (Moraes et al 2006).…”
mentioning
confidence: 99%
“…This industry sector discharges large volumes of brown colored effluents as a result of the different processes applied in wood and pulp bleaching, generating diverse pollutants [3,4]. The high chemical diversity of these pollutants causes a variety of clastogenic, carcinogenic and mutagenic effects on fish and other aquatic communities in recipient water bodies [5].…”
Section: Introductionmentioning
confidence: 99%